(untitled) (Journal of Applied Learning and Teaching, 2020)
Teaching and learning in the design studio aims to continuously offer the learner opportunities to relate their individual experience to the discourses shaping the professional field through an iterative process of inquiries, reflection and actions. This paper highlights the role of level-specific dialogue in the provision of design studio teaching at the early stages of the student’s journey toward professionalisation. It will be suggested that the Problem-Based Learning model enshrined in the idea of studio teaching alone does not facilitate for a sufficiently refined and truly reflective learning experience. By looking at a range of publications on the reflective practitioner, I hope to focus the discussion on the diachronic nature of dialogue in the disciplinary context of architectural education. The discussion of a number of case studies from the First Year provision at the CASS School of Architecture will illustrate a participatory approach to the dialogical scaffolding of early learning experiences and the assessment of generated outcomes as the conceptual framework of dialogical learning in the design studio. It will be argued that sustaining a dialogical process, based on multi-voiced provision, can contribute to the continuity of the learning experience at advanced levels of undergraduate studies, while critically addressing concerns raised about traditional studio teaching practices.